Dräktighetsdiabetes hos hund - Johansson Kreuger, Sanna (2008)
This article presents a retrospective case study combined with a review of the current literature concerning canine gestational diabetes. A total of 14 cases have been collected from six different clinics in Sweden. There are few previously published reports on canine gestational diabetes.